Anti-urolithiatic effect of Pericampylus glaucus against ethylene glycol induced urolithiasis in male sprague dawley rats - Kifayatullah, Muhammad; Rahim, Haroon; Jan, Naeem Ullah; Abbas, Sudhair; Khan, Muhammad Shahid; Ikram, Muhammad (Penerbit Universiti Kebangsaan Malaysia, 2019)
Pericampylus glaucus is a common plant used traditionally for the remedies of urinary and kidney stones. Hence, present research was aimed to investigate the antiurolithiatic effect of ethanol extract of P. glaucus against ethylene glycol induced urolithiasis in male Sprague Dawley rats. The nephrolithiasis was induced by ethylene glycol (0.75% v/v) in drinking water over a period of 30 days. The animals were divided into normal, lithiatic and extract treated group that received ethanolic extract of P. glaucus at dose rate of 200 and 400 mg/kg (b.wt) by mouth. The calcium, phosphate, urine pH, oxalate, magnesium in urine and histopathalogical examination of the kidney were observed. A significant (p<0.01) increased in the levels of phosphate, calcium, oxalate, and an imbalance in kidney with decreased magnesium excretion in urine were observed in ethylene glycol induced urolithiasis as compared to normal control. Treatment with ethanolic extract of P. glaucus at dose of 200 and 400 mg/kg (b.wt) decreased significantly (p<0.01) the hyperoxaluria, calcium, phosphate, oxalate with significant (p<0.05) increased retention of urinary magnesium and improvement in the renal function as matched to lithiatic group. The histopathological examination showed the deposition of a large number of calcium oxalate crystal in lithiatic group while smaller depositions in 200 mg/kg (b.wt) extract treated group. The results confirmed the antiurolithiatic effect of P. glaucus in male Sprague Dawley rats and validate its traditional uses against urinary stone.